The dragon in the sock drawer - Klimo, Kate.; Schroades, John (New York : Random House/ Yearling, 2008)
Cousins Jesse and Daisy always knew they would have a magical adventure, but they are not prepared when the "thunder egg" Jesse has found turns out to be a dragon egg that is about to hatch.
Keywords: Dragons -- Juvenile fiction; Animals -- Infancy -- Juvenile fiction; Cousins -- Juvenile fiction; Eggs -- Juvenile fiction